88.2k views
13 votes
Expand.
Your answer should be a polynomial in standard form.
(-p? - 4p - 3)(p2 + 2)

User Anefeletos
by
5.1k points

1 Answer

11 votes

Answer: Here is the answer.

Step-by-step explanation: we have to multiply each of the terms with the other terms.

=(-p²+4p-3)(p²+2)

=-p²*p²+ ( -p²*2) + 4p*p² + 4p*2 - 3*p²+ ( -3*2)

= -p³ -2p²+4p³+8p-3p²-6

=3p³-5p²+8p-6 (I grouped the like terms and added them)

therefore, 3p³-5p²+8p-6 is the polynomial in the standard form.

User Derek Lawrence
by
6.0k points